Factors influencing purchase intention of foreign apparel amongst millennials in South Africa - Chang, Maggie (University of the Witwatersrand, Johannesburg, 2023)
South Africa's clothing and fashion industry is perceived to be quite profitable, with over 800 apparel retailers nationwide. Most of the retailers sell apparel imported from various countries across the globe. Meeting the basic need of clothing trends is the most important factor driving this country's fashion and clothing industry Millennial tastes and preferences mostly drive fashion trends. This study, therefore, has a particular interest in investigating how millennials in South Africa, in particular, respond to foreign apparel and what factors influence them to choose imported apparel as opposed to local retailers by identifying the South African factors that millennial customers use to decide whether or not to buy from foreign clothing brands, assessing the impact of this decision on millennial customers' purchasing behaviour, and examining the drivers behind millennial customers' purchase behaviour. This paper used a sample of 797 anonymous respondents, and descriptive and quantitative analyses were carried out on the survey results. The results described the factors that affected the choice of foreign clothing brands by South African millennials, mainly focusing on the consumption group of South African millennials. The relevance and impact of various factors on millennials' purchase intention and purchase behaviour were shown through the data analysis of several factor variables. The purpose was to determine the influencing factors of millennials' purchase intention to buy foreign clothing brands in South Africa, and the analysis results proved consistent with the theoretical framework. This study found that disposable income, sustainable fashion, social media influence, and brand experience strongly impact purchase intention. Ethnic disparities adversely affected the purchase intention greatly. Purchase Intention also had a major positive impact on purchase behaviour. This study recommended that marketers and brand owners identify diverse client needs based on various customer attributes to satisfy South African consumers' varying and ever-changing wants for foreign apparel products
A research report submitted in partial fulfillment of the requirements for the degree of Master of Management in the field of Strategic Marketing (MM-SM) to the Faculty of Commerce, Law and Management, Wits Business School, University of the Witwatersrand, Johannesburg, 2023
Keywords: Foreign apparel; Millennial; Purchase intention; Purchase behaviour; UCTD; SDG-8: Decent work and economic growth